PELATIHAN DESAIN PENGEMASAN PRODUK DENGAN CANVA BAGI SISWA SMK NEGERI 1 PETANG - Yasa, I Wayan Adi Putra; Jayanegara, I Nyoman; Setiawan, I Nyoman Anom Fajaraditya; Yasa, Ngakan Putu Darma; Trisemarawina, I Nyoman Yoga; Anggara, I Gede Adi Sudi (Yayasan Lavandaia Dharma Bali, 2025)
The community service carried out aims to improve the ability of human resources at SMKN 1 Plaga related to students' abilities in utilizing and using information technology and improving students' understanding of product packaging. This activity is carried out in a series of supporting the P5 program as part of the Merdeka curriculum according to the government program. Using the knowledge transfer method about Canva and product packaging starting from designing labels, and box packaging to designing hampers. After being given a briefing on packaging materials, participants were given assignments in the form of projects to create product designs based on their interests and potential. Presentations and providing suggestions are the daily processes of this activity. The results of the service using the knowledge transfer method went well, participants participated enthusiastically with the results in the form of label designs, product packaging designs, and hampers designs from various products.